The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/s21020508
|View full text |Cite
|
Sign up to set email alerts
|

User-Cell Association for Security and Energy Efficiency in Ultra-Dense Heterogeneous Networks

Abstract: The last decades have been characterized by an exponential increase in digital services. The demand is foreseen to further increase in the next years, and mobile networks will have to mandatorily supply connections to enable digital services with very different requirements, from ultra high speed to ultra low latency. The deployment and the coexistence of cells of different size, from femto to macro, will be one of the key elements for providing such pervasive wireless connection: the ultra dense networks (UDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…18 User association and resource allocation optimization problem using deep learning algorithm in HetNets is investigated in Ding et al 19 Energy efficiency along with secure throughput objective is investigated by associating the user with a suitable BS using the heuristic algorithm by authors. 20 Joint user association and power allocation to maximize energy efficiency in HetNets employing deep reinforcement learning (DRL)-based approach has been studied in Hsieh et al 21 Solutions based on cloud services are adopting management systems with maximum EE to minimize energy consumption. A model has been purposed for Virtual Machines (VMs) to manage operations such as their placement, start-up, and migration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…18 User association and resource allocation optimization problem using deep learning algorithm in HetNets is investigated in Ding et al 19 Energy efficiency along with secure throughput objective is investigated by associating the user with a suitable BS using the heuristic algorithm by authors. 20 Joint user association and power allocation to maximize energy efficiency in HetNets employing deep reinforcement learning (DRL)-based approach has been studied in Hsieh et al 21 Solutions based on cloud services are adopting management systems with maximum EE to minimize energy consumption. A model has been purposed for Virtual Machines (VMs) to manage operations such as their placement, start-up, and migration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After looking at the Table 1 and going through past literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] to the best of the author's knowledge, it is concluded that joint users association and EE maximization for effective radio resource management in HetNets with macro and small cells assisted by relays and D2D has not been explored in the past. The main contributions of the proposed work are summarized below:…”
Section: Motivation and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques for power efficient community layout for wireless mobile network operations have been presented in the literature. In [3] grouped EE approaches into five categories, the majority of which coincide with those defined in [4] and [6]. These techniques are categorized into the five groups stated below.…”
Section: Udn Energy Efficiency Techniquesmentioning
confidence: 99%
“…In this context, there have been attempts to develop energy-efficient communications for CHNs [ 11 , 12 , 13 , 14 ]. In [ 11 , 12 ], resource allocations were investigated to maximize the energy efficiency of underlying device-to-device (D2D) communications, and, in [ 13 , 14 ], energy-efficient user-association methods were also investigated. To further improve the energy efficiency of CHNs, studies on multi-antenna techniques have been undertaken [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%